Effect of Seminal Plasma on Post‐Thaw Quality and Functionality of Corriedale Ram Sperm Obtained by Electroejaculation and Artificial Vagina - Ledesma, Alba; Manes, Jorgelina; Rios, Glenda Laura; Aller Atucha, Juan Florencio; Cesari, Andreina; Alberio, Ricardo; Hozbor, Federico Andres (Wiley, 2019)
We have already shown that seminal collection method affects seminal plasma composition and sperm quality in Corriedale rams. In this study, we evaluated the effect of seminal plasma collected by electroejaculation or artificial vagina on sperm resistance to cryodamage. Seminal plasma of five rams of the Corriedale breed collected by artificial vagina or electroejaculation was added before freezing to sperm cells collected by the two methods, and post‐thaw quality parameters were evaluated. We found that seminal plasma has no effect on sperm resistance to cryodamage. However, we observed significantly higher percentages of sperm with intact and functional plasma membrane, intact acrosome and greater fertilizing potential after thawing in samples obtained by electroejaculation. This study demonstrates that sperm collected by electroejaculation are more resistant to damage caused by cryopreservation than those collected by artificial vagina.